Pericoronary adipose tissue attenuation (PCAT) is associated with high-risk atherosclerotic plaque and subsequent acute coronary syndrome in patients with stable coronary artery disease. (25th November 2020) - Yuvaraj, J; Lin, A; Nerlekar, N; Munnur, R.K; Cameron, J; Nicholls, S.J; Wong, D.T.L
Abstract: Background: High-risk plaque (HRP) features detected on computed tomography coronary angiography (CTCA) are associated with subsequent development of acute coronary syndrome (ACS). Pericoronary adipose tissue attenuation (PCAT) is a novel CT-derived non-invasive marker of coronary inflammation. The association between PCAT, HRP and outcomes is unknown. Purpose: To evaluate the association between high-risk plaque HRP characteristics, ACS and PCAT attenuation as a surrogate marker of coronary inflammation. Methods: Patients with stable chest pain referred for CTCA between 2011 and 2013 with outcome data were included. Patients with HRP were propensity matched to patients without HRP. PCAT-RCA and PCAT-lesion were assessed using semi-automated software (AutoPlaque version 2.0). PCAT-RCA was measured around the proximal 10–50 mm of the right coronary artery (RCA). PCAT-lesion was measured around the HRP or lesion with highest-grade stenosis in patients without HRP. Results: 78 patients (67±10 years, 67% males) included 41 (52.6%) patients with HRP. Median PCAT-RCA was higher in HRP patients than non-HRP patients (−80.4 HU [IQR −86.1, −76.5] vs. −86.3 HU [IQR −92.2, −77.0], p=0.02). PCAT-Lesion was not significantly different between HRP and non-HRP patients (−78.7 HU [IQR −84.4, −73.4] vs. −82.8 HU [IQR −91.1, −75.4], p=0.16). More patients with HRP developed a subsequent ACS (24.4% vs. 5.4%, p=0.008). HRP patients who experienced an ACS demonstrated a higher PCAT-RCA (−76.6 HU [IQR −81.3, −72.4] vs. −82.6 HU [IQR −87.4, −78.0], p=0.018) and PCAT-lesion (−74.3 HU [IQR −77.1, −68.4] vs. −80.7 HU [IQR −84.8, −74.9], p=0.04) compared to those who did not experience an ACS. Conclusion: PCAT attenuation is elevated in stable CAD patients with HRP features. Measures of periarterial inflammation were also more evident in HRP patients who develop ACS, indicating a potential contribution to vulnerability. The implications for integration of these measures in clinical practice require further investigation. Funding Acknowledgement: Type of funding source: None